The relationship between HRM practices and career success - Tan, Fee Yean; Yahya, Khulida Kirana (2008)

(untitled)
The main purpose of this paper is to highlight the relationship between individual’s perception on the organizational HRM practices and career success. The three dimensions that measured perception on organizational HRM practices were compensation, performance appraisal, and training and development.While, the dimension that measured career success were subjective career success. In order to examine the relationship, a quantitative method was employed and questionnaires were used as an instrument.The sample of the study consists of 30 insurance agents representing two insurance agencies. Correlation analysis was used to examine the relationship between perception on HRM practices and career success.The results indicated that insurance agents’ perception on organizational HRM practices are significant predictor of their career success. The research and practical implications were also addressed.